Differential Effects of Exogenous Glomalin-Related Soil Proteins on Plant Growth of Trifoliate Orange Through Regulating Auxin Changes - Liu, Rui-Cheng; Gao, Wei-Qin; Srivastava, Anoop Kumar; Zou, Ying-Ning; Kuča, Kamil; Hashem, Abeer; Abd_Allah, Elsayed Fathi; Wu, Qiang-Sheng (Frontiers in Plant Science, 2021)
Multiple functions of glomalin released by arbuscular mycorrhizal fungi are well recognized, while the role of exogenous glomalins including easily extractable glomalin-related soil protein (EE-GRSP) and difficultly extractable glomalin-related soil protein (DE-GRSP) is unexplored for plant responses. Our study was carried to assess the effects of exogenous EE-GRSP and DE-GRSP at varying strengths on plant growth and chlorophyll concentration of trifoliate orange (Poncirus trifoliata) seedlings, along with changes in root nutrient acquisition, auxin content, auxin-related enzyme and transporter protein gene expression, and element contents of purified GRSP. Sixteen weeks later, exogenous GRSP displayed differential effects on plant growth (height, stem diameter, leaf number, and biomass production): the increase by EE-GRSP and the decrease by DE-GRSP. The best positive effect on plant growth occurred at exogenous EE-GRSP at ½ strength. Similarly, GRSP application also differently affected total chlorophyll content, root morphology (total length, surface area, and volume), and root N, P, and K content: positive effect by EE-GRSP and negative effect by DE-GRSP. Exogenous EE-GRSP accumulated more indoleacetic acid (IAA) in roots, which was associated with the up-regulated expression of root auxin synthetic enzyme genes (PtTAA1, PtYUC3, and PtYUC4) and auxin influx transporter protein genes (PtLAX1, PtLAX2, and PtLAX3). On the other hand, exogenous DE-GRSP inhibited root IAA and indolebutyric acid (IBA) content, associated with the down-regulated expression of root PtTAA1, PtLAX1, and PtLAX3. Root IAA positively correlated with root PtTAA1, PtYUC3, PtYUC4, PtLAX1, and PtLAX3 expression. Purified EE-GRSP and DE-GRSP showed similar element composition, but varied in part element (C, O, P, Ca, Cu, Mn, Zn, Fe, and Mo) concentration. It concluded that exogenous GRSP triggered differential effects on growth response, and the effect was associated with the element content of pure GRSP and the change in auxins and root morphology. EE-GRSP displays a promise as a plant growth biostimulant in citriculture.